Sexual Well-Being in Patients with Blepharospasm, Spasmodic Torticollis, and Hemifacial Spasm: A Pilot Study - Perozzo, Paola; Salatino, Adriana; Cerrato, Paolo; Ricci, Raffaella (Frontiers in Psychology, 2016)
Mood, anxiety and other psychological symptoms are common in dystonic patients suffering from blepharospam (BSP) and spasmodic torticollis (ST). Since sexual well-being is an important aspect of mental health, here, we investigated whether these patients may also experience a worsening of their sexual life. In particular, quality of sexual life was evaluated in patients suffering from BSP (N=30), ST (N=30), and in a control group of patient with Hemifacial spasm (HFS; N=30), undergoing botulinum toxin type A therapy. A group of 30 age-matched healthy volunteers constituted an additional control group. Patients were evaluated just before the periodic injection of botulinum toxin. Sexual functioning was assessed using the Sexual Functioning Inventory (SFI), a reduced form of the Gollombok Rust Inventory, previously employed in patients with Parkinson’s disease. Depression (Beck Depression Inventory) and anxiety (STAI-X1/X2) were also assessed. Results revealed that sexual functioning was significantly affected in patients with BSP, ST, and HFS with respect to healthy controls. Dystonic patients manifested more sexual dysfunction than patients with HFS. Overall, females had a poorer quality of sexual life than males and, among females, women with BSP were the most dysfunctional. Psychological symptoms were present in patients with dystonia, but not in patients with HFS. As discussed in the paper, several factors might be taken into account to explain worse quality of sexual life in patients with dystonia compared to patients with hemifacial spasm. Among them an important role might be played by the central origin of dystonia pathophysiology (i.e. altered activity of cortico-striato-thalamic-cortical circuits). Future investigations are necessary to further explore these preliminary findings, considering that this is the first time that sexual well-being is evaluated in patients with BSP, ST and HFS, and comparable data are not available.